Preservation of maize (Zea mays L.) seeds by Cuminum cyminum fruit essential oil - KUMAR, NARENDRA (Indian Phytopathology, 2016)
Samples of maize (Zea mays L.) seeds were collected from farmer stores and examined for mycobiota. Sixteen species of fungi were identified by blotter method and 13 species of fungi by agar plate method. In vitro volatile constituents extracted in the form of essential oils from 32 plant species were evaluated against the dominant fungi, Aspergillus flavus and Aspergillus niger. The oil of Cuminum cyminum (Apiaceae) exhibited the greatest toxicity. The oil was found to be fungicidal and thermostable at its minimum inhibitory concentration (MIC) of 300 ppm. The oil was characterized by the determination of its various physico-chemical properties. In vivo studies depict that the oil as seed dressing agent and as a fumigant was able to preserve the maize food seeds completely for 5 months at 0.50 and 0.76 mL in containers of 1000 mL capacity holding 1 kg seeds with minimal changes in organoleptic behavior. It did not exhibit any adverse effect on seed germination, seedling growth and general health and morphology of plants.